Enhancing Hydro-Spatial Reasoning through a Non-Linear Prezi Framework for Localized Flood Mitigation Education in Kediri City - Asri Dyah Kumalasari; Listyo Yudha Irawan; Yusuf Suharto; I Komang Astina (Future Space: Studies in Geo-Education, 2026)
While traditional instruction often relies on linear narratives, this study examines how Prezi’s dynamic contextualized through localized flood phenomena in Kediri City enable students to synthesize multi-dimensional environmental risks and adaptation strategies. The research addresses the critical gap in contextual disaster education within the flood-prone Brantas watershed. Adopting a systematic 4D developmental methodology (Define, Design, Develop, and Disseminate), the study encompasses a rigorous needs analysis, instructional design, and empirical trials. The sample involved 32 Grade XI students at SMAK St. Augustinus Kediri and a panel of expert validators. Data were synthesized through Likert-scale questionnaires and qualitative expert feedback to evaluate pedagogical validity and the resultant cognitive transitions. Empirical findings identify a distinct cognitive shift 87% of students demonstrated an advanced ability to correlate Kediri’s flat topography with local inundation susceptibility. Beyond surpassing the 80% validation threshold from subject-matter and media experts, the framework significantly increased active participation in spatial discussions. Participants successfully mapped connectivity between upstream land-use transformations in the Brantas watershed and downstream urban flood risks. The Prezi-based media optimizes geospatial literacy by utilizing a navigation architecture that visualizes the complex connectivity between regional hydro-spatial dynamics and local vulnerabilities. This facilitates a transition from passive consumption to applied spatial reasoning, effectively supporting the Independent curriculum’s objectives. The media demonstrates high pedagogical utility, subsequent iterations should enrich narrative depth and increase the complexity of evaluative tasks to optimize long-term knowledge retention.